2016
DOI: 10.1186/s40538-016-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Penicillium bilaii on wheat growth and phosphorus uptake as affected by soil pH, soil P and application of sewage sludge

Abstract: Background: Penicillium bilaii may enhance P availability to plants, since it has been shown to increase plant growth and P uptake. There is currently increasing interest in using microorganisms to promote P mobilisation from organic P sources. An investigation was conducted to determine the effects of P. bilaii on P uptake and growth of wheat in the presence and absence of sewage sludge. Two soils differing in P contents and pH were used, as it was hypothesised that these affect the efficiency of P mobilisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Although the reasons for the suboptimal performance of the nursery plants in our studies are not entirely clear, the mitigation effect of BS applications is obvious (Figure 1) and may therefore, offer a perspective for optimization of nursery substrates frequently used also used in organic tomato production. Accordingly, for many of the microbial inoculants used in this study, root growth promoting and P-solubilizing properties are well documented [21,22,[31][32][33][34]. The same holds true for priming effects against various abiotic and abiotic stresses [20,21,[35][36][37] with protective effects also against potential substrate toxicities.…”
Section: Nursery and Vegetative Growthmentioning
confidence: 95%
“…Although the reasons for the suboptimal performance of the nursery plants in our studies are not entirely clear, the mitigation effect of BS applications is obvious (Figure 1) and may therefore, offer a perspective for optimization of nursery substrates frequently used also used in organic tomato production. Accordingly, for many of the microbial inoculants used in this study, root growth promoting and P-solubilizing properties are well documented [21,22,[31][32][33][34]. The same holds true for priming effects against various abiotic and abiotic stresses [20,21,[35][36][37] with protective effects also against potential substrate toxicities.…”
Section: Nursery and Vegetative Growthmentioning
confidence: 95%
“…phytohormones) by the PSM. Stimulation of root growth through phytohormones provides plants with greater access to soil P (through increased root–soil contact) and thus typically results in an indirect ‘apparent’ P benefit without a direct effect of PSM on P availability both under controlled and field conditions (Gulden & Vessey, 2000; Wakelin et al ., 2005; Sánchez‐Esteva et al ., 2016; Gómez‐Muñoz et al ., 2017; Meyer et al ., 2017; Sarabia et al ., 2018; Liu et al ., 2019; Hansen et al ., 2020).…”
Section: Phosphate Solubilisation In Vitro: Can These Mechanisms Occumentioning
confidence: 99%
“…Sánchez‐Esteva et al . (2016) compared the ability of P. bilaiae to improve wheat productivity in an acidic soil (pH H20 5.5) and in a calcareous soil (pH H20 8.2) and found that plant biomass only increased in calcareous soil. In another study, Wakelin et al .…”
Section: Factors Potentially Affecting Success or Failure Of Psm Inoculationmentioning
confidence: 99%
“…In particular, Penicillium bilaii has been reported to solubilise phosphorus (P) under different conditions (Asea, Kucey, & Stewart, ; Kucey, ) and to increase plant growth and yield in wheat (Gleddie, Hnatowich, & Polonenko, ), bean (Kucey, ), oilseed rape (Kucey & Leggett, ), pea (Downey & van Kessel, ), lucerne (Beckie, Schlechte, Moulin, Gleddie, & Pulkinen, ) and maize (Leggett et al., ). In previous studies, we observed an increase in root growth in maize (Gómez‐Muñoz, Pittroff, et al., ) and wheat (Sánchez‐Esteva, Gómez‐Muñoz, Jensen, de Neergaard, & Magid, ) inoculated with P. bilaii , which could increase plant growth by better meeting plant nutrient demand (Liu et al., ). Exogenous salicylic acid could be another solution to mitigate the adverse effect of cold stress in early stages of maize growth.…”
Section: Introductionmentioning
confidence: 74%